Impact of Female Sex on Clinical Outcomes in the FIRE AND ICE Trial of Catheter Ablation for Atrial Fibrillation. (May 2018) - Kuck, Karl-Heinz; Brugada, Josep; Fürnkranz, Alexander; Chun, K.R. Julian; Metzner, Andreas; Ouyang, Feifan; Schlüter, Michael; Elvan, Arif; Braegelmann, Kendra M.; Kueffer, Fred J.; Arentz, Thomas; Albenque, Jean-Paul; et al.
Abstract : Background: Data on predictors of long-term clinical outcomes after catheter ablation of atrial fibrillation (AF) are limited. We sought to assess the association of baseline covariates with clinical outcomes in the 750 patients with drug-refractory paroxysmal AF enrolled in FIRE AND ICE. Methods: In a 2-part analysis, univariate and multivariable Cox regression models were first used to identify baseline patient characteristics predictive of catheter ablation efficacy determined by the clinical end points of (1) atrial arrhythmia recurrence (primary efficacy failure), (2) cardiovascular rehospitalization, and (3) repeat ablation. Propensity score stratification methods were then used to account for differences in baseline characteristics between sexes. Results: Female sex (hazard ratio [HR], 1.37; 95% confidence interval [CI], 1.08–1.73; P =0.010) and prior direct current cardioversion (HR, 1.40; 95% CI, 1.07–1.82; P =0.013) were independently associated with atrial arrhythmia recurrence. Female sex (HR, 1.36; 95% CI, 1.02–1.80; P =0.035) and hypertension (HR, 1.48; 95% CI, 1.09–2.00; P =0.013) independently predicted cardiovascular rehospitalization. A longer history of AF (HR, 1.03; 95% CI, 1.00–1.06; P =0.039) increased the rate of repeat ablation. Women continued to have higher rates of primary efficacy failure and cardiovascular rehospitalization after propensity score adjustment, with adjusted HRs of 1.51 (95% CI, 1.16–2.18; P <0.05) and 1.40 (95% CI, 1.15–2.17; P <0.05), respectively. Conclusions: After catheter ablation of paroxysmal AF, female sex was associated with an almost 40% increase in the risks of primary efficacy failure and cardiovascular rehospitalization. Primary efficacy failure was also adversely impacted by a history of direct current cardioversion, whereas hypertension had a negative impact on cardiovascular rehospitalization. History of AF was the only predictor of repeat ablation. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01490814. Abstract : Supplemental Digital Content is available in the text.